Do Differences in the Colour and Phenolic Composition of Young Shiraz Wines Reflect During Ageing? - de Beer, P.; Strever, A.; du Toit, W.J. (South African Journal of Enology and Viticulture, 2017)
This study investigated the evolution of colour and phenolic compounds of Shiraz wines during wine ageing. Wines made from the same vineyard, but with a different phenolic composition, were used in this study. Analyses included colour density, anthocyanins, tannin, hydroyxycinnamic acids, flavan-3-ols, polymeric pigments and polymeric phenols. Differences in phenolic compositions observed in the young wines were generally still observed after 6 and 12 months of ageing. These results indicate that significant differences in terms of phenolics and colour in young Shiraz red wines might thus be expected to be reflected in the wines after ageing as well.